Energy project management system: benefits, principles and risks - Dedeliuk, Kateryna Yu.; Деделюк, Катерина Юріївна (Національний технічний університет "Харківський політехнічний інститут", 2016)
The essence of an effective energy project management system was described, as well as the main benefits of its implementation at the company level were characterized. Such outcomes as possible savings unlocking, improving risk management, reliability and productivity, reputational issues where described as key results from realization of an energy project management system. Among the main principles according to which an effective energy project management should be implemented the fallowing aspects were discussed: leadership and responsibility, energy policy and energy performance, communication and continuity of energy policy. The conclusions about the main risks that may occur during implementation of an effective energy project management system were also systematized in this article.
Keywords: project; management system; energy project; risks; principles; risks